IMPLEMENTASI PROGRAM BIMBINGAN BELAJAR DALAM MENDORONG MODERASI BERAGAMA PADA ANAK DI DESA TANJUNG HARAPAN KECAMATAN SEPUTIH BANYAK - Aslihatus Nawang Sa'diyah; Ayesha Hanifatuz Zahrani; Dara Fatikha Sabilah Hasanah; Dedah Hidayanti; Fredy Gandhi Midia (JPMUJ, 2024)
The purpose of this article is to examine how religious modernization in Tanjung Harapan Village, Seputih Banyak District, Central Lampung Regency is influenced by the Community Service Program (KKN). Even though the majority of the residents of Tanjung Harapan Village are Muslim, they still adhere to traditional interpretations of Islam. The Tanjung Harapan Village Community Service Program seeks to increase religious tolerance in everyday life. The community is involved in the research process through Participatory Action Research (PAR) techniques. The Tanjung Harapan Village community was involved in the design, implementation and assessment of the KKN program in this research. Research findings show that the KKN program implemented in Kebonrejo Village has increased religious moderation in the village. Children in Tanjung Harapan Village are given an understanding of religious tolerance and moderation with a deeper understanding of Islamic principles, children in Tanjung Harapan Village are now better prepared to overcome social inequality and tolerate a wider range of religious beliefs.